Development and verification of the functioning of genetic constructs for DNA vaccine against porcine circovirus type 2 - Kravchenko, Lidia M.; Prakulevich, Uladzimir A.; Kudzin, Kiryl V. (Experimental Biology and Biotechnology, 2018)
In this research a design of two genetic constructions which may be used for creation of DNA vaccine for porcine circovirus type 2 (PCV-2) was developed. This constructions were derived from commercial plasmid vector pVAX 1, one of them contains full-size natural open reading frame of circovirus capsid protein and the second contains an open reading frame corresponding to a protein without the first thirty N-terminal amino acids. The appropriate primers for amplification of the necessary viral protein fragments were developed. Expression of the target sequences was detected by the presence of the virus capsid protein in the culture of transfected mammalian cells. Preliminary possibility of calcium-phosphate transfection of the porcine cell line SPEV was assessed. The obtained results showed that this approach is inexpedient for further studies of target genetic constructs. The results of the experiments showed that the circovirus capsid protein is present in the lysates of transfected cells in low amounts, while the content of the truncated variant of the protein is higher than the native one.